Football: the importance of the media in the popularization and imaginary of the Brazilian - Kupper, Agnaldo [UNESP] (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2019)
In the transition from Brazilian society to an urban life, football has gained proportion of sport group identifier through the expansion of public space. In the process of urbanization, streets were being inhabited and social gatherings became more frequent. In this sense, the hitherto elite sport has become one of the main leisure activities of the population, leading to new behaviors. It is important to reflect on the role of the sports press in the formation of national identity and in the construction of memory through the rescue of images, facts, successes and failures, even because the action of the sports press forms traditions through appropriations from the past.
Keywords: Football; Imaginary; Media